Conservation of Medicinal Plant Resources in Himalayas (India) - Goel, C. L. (Indian Forester, 1993)
The Himalayas are a rich source of medicinal plants which have generated tremendous scope of employment opportunities for local inhabitants apart from their role in health care system of the country and other socio-economic and environmental impacts on not only the local populations of these natural resources over several decades has brought us to the verge of loosing some of these precious heritage thereby also contributing to the general disintegration of our environment. The present article is an attempt to highlight the role these resources play in our daily life and national economy; the need to conserve these resources; and the strategies for such conservational actions at the national and individual level.